2021
DOI: 10.1108/aeat-11-2020-0263
|View full text |Cite
|
Sign up to set email alerts
|

Aeroacoustic and aerodynamic characteristics of a morphing airfoil

Abstract: Purpose This paper aims to assess the aeroacoustic and aerodynamic performance of a morphing airfoil with a flexible trailing edge (FTE). The objective is to make a comparison of the aerodynamic noise characteristics between the conventional airfoil with a flap and morphing airfoil and analyse the noise reduction mechanisms of the morphing airfoil. Design/methodology/approach The computational fluid dynamic method was used to calculate the aerodynamic coefficients of morphing airfoil and the Ffowcs-Williams … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Research advises modification over the wing surface will act as a flow control device (Arivoli and Ishan, 2016; Bofeng et al , 2018; Kang et al , 2020; Arunvinthan et al , 2020; Serder Genc and Kaynak, 2009). The wing combination of gurney flap at the leading edge and divergent trailing edge is tested and reported to improve aircraft aerodynamic efficiency (Li et al , 2006; Zi kan et al , 2021). Cheng and Wang (2018), Serder Genc and Kaynak (2009) demonstrated that increasing the wing surface area will increase the lift generated by the wing.…”
Section: Introductionmentioning
confidence: 99%
“…Research advises modification over the wing surface will act as a flow control device (Arivoli and Ishan, 2016; Bofeng et al , 2018; Kang et al , 2020; Arunvinthan et al , 2020; Serder Genc and Kaynak, 2009). The wing combination of gurney flap at the leading edge and divergent trailing edge is tested and reported to improve aircraft aerodynamic efficiency (Li et al , 2006; Zi kan et al , 2021). Cheng and Wang (2018), Serder Genc and Kaynak (2009) demonstrated that increasing the wing surface area will increase the lift generated by the wing.…”
Section: Introductionmentioning
confidence: 99%